The Diagnosis of Gestational Diabetes Mellitus: A Comprehensive Systematic Review - Haryanto; Pratono (International Medical Journal Corp. Ltd, 2024)
Background: Gestational diabetes mellitus (GDM) is any degree of glucose intolerance with onset or first recognition during pregnancy. GDM can classify as A1GDM and A2GDM. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. The literature was compiled using PubMed, ScienceDirect, and SagePub, among other online venues. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Pregnancy insulin resistance or hypertriglyceridemia may be useful in GDM risk stratification. Future studies examining non-glycemic biochemical, genetic, other -omic, or sociocultural precision markers among women with GDM are warranted.